The infinitude of beauty as expression of the beauty of the infinite? : a critical evaluation of the use of the analogia entis in the theological aesthetics of David Bentley Hart - Havenga, Marthinus Johannes (Stellenbosch : Stellenbosch University, 2014)
Thesis (MTh)--Stellenbosch University, 2014.